Focal cryoablation: a treatment option for unilateral low‐risk prostate cancer. (31st October 2013) - Durand, Matthieu; Barret, Eric; Galiano, Marc; Rozet, François; Sanchez‐Salas, Rafael; Ahallal, Youness; Macek, Petr; Gaya, Jose‐Maria; Cerruti, Jennifer; Devilliers, Hervé; Loeffler, Joyce; Amiel, Jean; et al.
<x xml:space="preserve">Abstract</x> Objectives To assess oncological (biochemical and histological recurrence) and functional (urinary and potency) outcomes in patients with unilateral low‐risk organ‐confined prostate cancer (PCa) treated with focal cryoablation (FC). Patients and Methods From January 2009 to March 2012, patients with localized PCa who refused active surveillance were assigned to a FC protocol. This was a prospective, single‐arm cohort study. Inclusion criteria were: unilateral disease, clinical stage T1c to T2a, prostate‐specific antigen (PSA) concentration <10 ng/mL, low volume index lesion and Gleason score ≤6 (3+3). Hemi‐ablation was carried out using the PreciseTM cryoablation system (Galil Medical, Inc., Arden Hills, MN, USA). Oncological (PSA values) and functional (International Prostate Symptom Score and International Index of Erectile Function (IIEF)‐5 score) outcomes were analysed at 3‐, 6‐ and 12‐month follow‐up. The primary endpoint for oncological efficacy, no cancer in ipsilateral side, was based on the 12‐month mandatory biopsy. Results A total of 48 consecutive patients with a mean age of 67 years were included. The median (interquartile range) follow‐up was 13.2 (7.4–26.5) months. Follow‐up prostate biopsies were negative for the treated lobe in 86% of patients. The mean PSA concentration dropped significantly at 3 months (by 55%) but did not correlate well with positive biopsy results. Urinary symptoms were unchanged. A slight decrease in the IIEF‐5 score was present at 3 months, but did not differ significantly from baseline at 6‐month follow‐up. There were 15% grade 1 and 4% grade 2 complications (Clavien classification). Conclusions Focal cryoablation is a low‐morbidity option in selected patients with low‐risk PCa. We showed PSA concentration to be an unreliable marker for monitoring FC and recommend a protocol of mandatory biopsies for follow‐up. A multicentre randomized controlled trial is necessary to confirm the low‐morbidity and the biopsy‐proven PCa cure rates.